The effect of area loading and punching shear on the reinforced concrete slab containing spherical plastic bubble balls - Nor Ashikin, Muhamad Khairussaleh; Hoe, Ng Kah; Parke, G.A.R.; Roslina, Omar (Trans Tech Publications, Switzerland, 2022)
The reinforced bubble deck slab or BubbleDeck is a unique system that improves the building design and performance of structures. This slab structure is a reinforced concrete structure that contains high-density polyethene (HDPE) hollow spherical plastic bubble balls with less concrete volume compared to a normal reinforced concrete slab. The system can facilitate up to a 50% longer span compared to a conventional reinforced concrete solid slab. But, eliminating the deadweight concrete may affect the actual performance of the slab structure such as its flexural and shear capacity. Thus, this paper investigates the effect of area loading and punching shear loading on the reinforced bubble deck slab in terms of flexural performance. The square slabs with 1200mm by 1200mm for width and length with a thickness of 230mm were designed as a one-way supported slab. A total of 36 HDPE hollow spherical plastic bubble balls with a 180mm diameter were placed in each bubble deck slab specimen. The high yield steel DA6 BRC reinforcement steel bar meshes and Grade-30 concrete were used for the slabs. The experimental results of the flexural performance of the reinforced bubble deck slab that were subjected to the static area and punching shear loadings are presented. The effect of the load applied in the experiments on the slabs such as flexural strength, bending stiffness and load-deflection behaviour were discussed including the crack propagation and crack pattern.